Maine woods Quest - Young, Christine; Maine Public Television ([Lewiston, Me.] : Maine Public Television, 1995)
This program surveys the climate and soil conditions that make Maine heavily forested, the historical role of lumbering in Maine's economy, and scientific issues involved in clearcutting.
Hosted by Christine Young.
VHS.
Closed-captioned.
Keywords: Forest management -- Maine; Forest policy -- Economic aspects -- Maine; Sustainable forestry -- Maine; Video recordings for the hearing impaired